EFFECT OF CLONIDINE ADDED TO CAUDAL ROPIVACAINE IN PEDIATRIC INFRAUMBILICAL SURGERIES - Solanki, Dr. Nilesh M.; Rathod, Ajay; Maheshwari, Khevana; Bhimani, Maulik (Bali Journal of Anesthesiology, 2018)
Â Background: Caudal epidural block is the most popular regional anesthesia technique in pediatrics. Several agents are required as an adjuvant with a local anesthetic to prolong the duration of caudal analgesia by single shot technique in children. The aim of this study was to compare the efficacy of clonidine with ropivacaine versus ropivacaine alone for caudal analgesia in children undergoing infraumbilical surgeries under general anesthesia.Methods: Sixty patients of ASA grade I â II between the ages of 1-12 years, of either sex, undergoing infraumbilical surgeries under general anesthesia were included randomly into two groups: Control group (Group A) ropivacaine 0.2% (1ml/kg) with maximum volume 12 ml and clonidine group (Group B) ropivacaine 0.2% (1ml/kg) with clonidine 1Âµg/kg with maximum volume 12 ml. The changes of hemodynamic parameters were recorded intraoperatively. The FLACC pain score, sedation score, duration of analgesia and requirement of analgesic were recorded in the recovery room.Results: The demographic characteristic were comparable in both the groups. The mean duration of analgesia was significantly prolonged (707.3 + 59.56 minutes) in group B compared to (411.83 + 14.82 minutes) in group A.Â  The requirement of first rescue analgesic medication was significantly prolonged in group B compared to group A (P < 0.05). Total analgesic consumption was significantly higher in group A (180+70 mg) compared to group B (90+70 mg) (P < 0.05)Conclusion: Addition of clonidine 1Âµg/kg to ropivacaine 0.2 % in caudal analgesia significantly increases the duration of postoperative analgesia compared to plain ropivacaine 0.2% without any significant sedation.